To solve for the missing exponent in the equation \( e^? \cdot e^{65} = e^{38} \), we can use the property of exponents that states \( e^a \cdot e^b = e^{a+b} \).
Using this property, we can rewrite the left side of the equation:
\[ e^? \cdot e^{65} = e^{? + 65} \]
Now we can set the exponents equal to each other from both sides of the equation:
\[ ? + 65 = 38 \]
To find \( ? \), we can subtract 65 from both sides:
\[ ? = 38 - 65 \]
Calculating this gives:
\[ ? = -27 \]
Thus, the missing exponent is \( -27 \).